Perspectives, Factors of Influence, and Previous Experiences Related to Teaching English in Primary Schools, Inside and Outside Algeria. - djouiba, choayb (Journal of Social Sciences and Humanities, 2024)
In today's Arab world, English has become an indispensable tool for trade and economics. Algeria, as part of the Arab world, has recognized the necessity of cultivating a new generation proficient in the English language to drive the development of various sectors, with education standing out as the primary beneficiary of this proficiency, by the official implementation of English for the first time in primary schools. This comprehensive research paper delves into the multifaceted landscape of English language education in primary schools, both within and beyond the borders of Algeria. It explores a diverse array of perspectives, influential factors, and past experiences related to the teaching of English in primary educational settings. The paper sheds light on the global significance of English as a medium of international communication and opportunity, emphasizing its pivotal role in scientific and technological advancement. Additionally, it investigates the imperative of teaching English in Algeria, examining the perspectives of parents and teachers, as well as the readiness of educators to integrate 21st-century skills into English language instruction. Furthermore, the paper explores factors that influence the learning process in primary schools, including students' interest in English learning, family dynamics, and personal qualities. Drawing on previous experiences from diverse educational contexts, the paper offers valuable insights and recommendations for the effective implementation of English language education in primary schools. This research contributes to a deeper understanding of the challenges and opportunities associated with English language education and aims to inform educational policy and practice in Algeria and beyond.